2022
DOI: 10.3389/fmicb.2022.832893
|View full text |Cite
|
Sign up to set email alerts
|

Application of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry for the Rapid Identification of Yeast Species From Polar Regions

Abstract: Protein profiling based on matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) has proved to be a powerful tool for yeast identification. However, it is rarely used in the identification of yeast isolates from polar regions, which may be due to the limited data available for the differentiation of polar yeast species. The present study constructed a supplementary database of MALDI-TOF MS, including 33 yeast species from the Arctic and Antarctica. These yeast species we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Each spectrum was generated using 240 laser shots (six series of 40 laser shots) and with linear positive mode over a mass range of m/z 2,000–20,000. The Autof ms1000 mass was calibrated prior to analysis using a calibrating agent (containing Escherichia coli DH5α, ribonuclease, and myoglobin; Autobio Diagnostics, China) as described by He et al (2022) . The spectral data yielded from the test strains were then compared to the database to obtain a score.…”
Section: Methodsmentioning
confidence: 99%
“…Each spectrum was generated using 240 laser shots (six series of 40 laser shots) and with linear positive mode over a mass range of m/z 2,000–20,000. The Autof ms1000 mass was calibrated prior to analysis using a calibrating agent (containing Escherichia coli DH5α, ribonuclease, and myoglobin; Autobio Diagnostics, China) as described by He et al (2022) . The spectral data yielded from the test strains were then compared to the database to obtain a score.…”
Section: Methodsmentioning
confidence: 99%
“…Due to MALDI-TOF MS being able to detect a variety of pathogens rapidly, it has extensively been employed to identify microorganisms, such as bacteria, yeasts and molds, from clinical samples routinely [ 15 ]. Several studies have reported that this technique is rapid and exhibits high accuracy in fungal identification from clinical and environmental specimens [ 16 , 17 , 18 ]. It has also been implemented for biological, clinical, and biotechnological research.…”
Section: Introductionmentioning
confidence: 99%